African American civil rights movement. - World Book, Inc. (Chicago World Book, 2011)
"A history of the African American civil rights movement, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.
Keywords: African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Sources -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Sources -- Juvenile literature; United States -- Race relations -- Juvenile literature; United States -- Race relations -- Sources -- Juvenile literature